Implementation of Genre-Based Approach in Teaching Letter Writing to Seventh Grade Students at MTs Al Ihsan Condet, East Jakarta - Sulistio, Bagus (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This research aims to describe the writing abilities of seventh-grade students at MTs Al Ihsan Condet through a Genre-Based Approach in teaching letter writing. This approach involves five main steps: building context, modeling, joint construction, independent construction, and connecting related texts. The research method used is descriptive qualitative, with data collected through observations and interviews with teachers and students. This approach allows researchers to describe the learning phenomenon factually and gain deep insights into the processes and challenges faced. The results show that although students can participate in writing activities using this method, the implementation of the Genre-Based Approach still encounters several challenges. Teachers have difficulty effectively implementing the steps, and students find letter writing to be a continuing challenge. However, this method helps students understand the theory of letter writing through meaningful practical experiences. Genre-Based Approach has great potential to improve students' writing skills if implemented more effectively. With a deeper understanding and adjustments in application, this approach can become a very effective method for teaching letter writing in schools. Improvements in the implementation of each step will significantly contribute to overcoming the difficulties faced and enhancing students' learning outcomes in writing skills.